3D Macro Physical Experiment of Matrix-Fracture Interaction Flow in Fractured Reservoirs - Zupeng, Ding; Yuetian, Liu (Physical and Numerical Simulation of Geotechnical Engineering, 2017)
The imbibition interaction phenomenon exists between the matrix system and the fracture system during the waterflooding process in fractured reservoirs. And the physical experiment method is an important way to study the matrix-fracture interaction flow laws. Quantitative control of the fracture physical parameters distribution and that of the matrix-fracture imbibition interaction parameters are achieved by using the accurate bonding manufacture technique of fractured porous media and the incomplete vacuum saturation technique, respectively. Based on these methods, a three-dimensional physical model is established. And then the macro flow laws of fractured porous media with matrix-fracture imbibition interaction are studied. The experiment results are macro displays of the matrix-fracture imbibition interaction. And the experiment can be a reference for studies on matrix-fracture interaction flow laws in fractured reservoirs.